Military Politisation from President Soekarno's Era to President Jokowi - A'dila; Jajang Wawan Setiyawan; Muhammad Fauzi Rizki; Muhammad Rizal Arifin Hidayah (Social Impact Journal, 2022)
This research is a study of how the military has strong influence and power in the political map in Indonesia. This study aims to review the dynamics of the military from the Soekarno regime to Jokowi. The method used is a literature study research method. Methods of collecting library data, reading, and taking notes also analyze research materials and collect secondary data. The results of this study show that during the Soekarno regime the influence of the military in politics had appeared, then during his leadership period the concept of the "middle way" was initiated by A.H. Nasution as a military strengthening power in politics. Entering the Soeharto regime, the concept of "middle way" became a stimulus for the practice of the Dwifungsi ABRI and in this regime the military dominated the leading sector of government. During the Habibie regime there was military controversy, but Habibie had military reform efforts with the aim of efficiency, professionalism and improving the military's reputation. Gus Dur's regime took various bold actions in intervening in the internal military because Gus Dur wanted civilian supremacy and a reduction in the role of the military. Megawati's leadership changed the view of the military in ruling the government, the army has carried out reforms towards military professionalism. SBY's regime civil-military relations became more harmonious, civilian supremacy and military professionalism were given more attention. The Jokowi regime illustrates that military politics has returned to the surface, with retired officers holding strategic positions back in the Jokowi era. The politicization of the military in Indonesia has found a dynamic reality in practice, since the Soekarno era until Jokowi there has been no clear standard in using or building certain civil-military relations